Equine Trypanosomiasis: Molecular Detection, Hematological, and Oxidative Stress Profiling - Mostafa Shoraba; Salma A. Shoulah; Faysal Arnaout; Abdelfattah Selim (Veterinary Medicine International)
Surra caused by Trypanosoma evansi (T. evansi) is widely distributed and has significant impact on equine sector and international trades. However, there are no available data about the genetic characterization of this parasite in horses in Egypt. So, the goal of this study was to study the molecular characterization of T. evansi in horses and determine the changes in hematological parameters and oxidative stress associated with T. evansi infection. A total of 12 horses were examined using PCR targeting RoTat 1.2 VSG gene, and we evaluated the changes in hematological and oxidative stress between infected and healthy animals. The results revealed a notable reduction in red blood cell (RBC), hematocrit (HCT), and hemoglobin (Hb) levels in the infected horses, as compared to the control healthy group. In contrast, the infected group showed a substantial increase in mean corpuscular hemoglobin concentration (MCHC), mean corpuscular hemoglobin (MCH), and mean corpuscular volume (MCV). In addition, the infected group exhibited monocytopenia, eosinopenia, and notable lymphocytopenia. Regarding oxidative stress profile, the infected horses showed decreased levels of glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and antioxidant capacity (TAC) compared to the control group. Moreover, the PCR assay targeting RoTat 1.2 VSG gene revealed positive specific band (205 bp) in all examined samples for T. evansi and the phylogenetic analysis demonstrated that strain of this study is closely related to T. evansi isolate in horses from India (MT501210) while showed difference from sequences of other species. The results emphasize the changes in blood composition and the body’s response to oxidative stress caused by T. evansi infection in horses.